Transport capabilities of environmental Pseudomonads for sulfur compounds. (10th February 2017) - Zerbs, Sarah; Korajczyk, Peter J.; Noirot, Philippe H.; Collart, Frank R.
Abstract: Sulfur is an essential element in plant rhizospheres and microbial activity plays a key role in increasing the biological availability of sulfur in soil environments. To better understand the mechanisms facilitating the exchange of sulfur‐containing molecules in soil, we profiled the binding specificities of eight previously uncharacterized ABC transporter solute‐binding proteins from plant‐associated Pseudomonads. A high‐throughput screening procedure indicated eighteen significant organosulfur binding ligands, with at least one high‐quality screening hit for each protein target. Calorimetric and spectroscopic methods were used to validate the best ligand assignments and catalog the thermodynamic properties of the protein‐ligand interactions. Two novel high‐affinity ligand‐binding activities were identified and quantified in this set of solute‐binding proteins. Bacteria were cultured in minimal media with screening library components supplied as the sole sulfur sources, demonstrating that these organosulfur compounds can be metabolized and confirming the relevance of ligand assignments. These results expand the set of experimentally validated ligands amenable to transport by this ABC transporter family and demonstrate the complex range of protein‐ligand interactions that can be accomplished by solute‐binding proteins. Characterizing new nutrient import pathways provides insight into Pseudomonad metabolic capabilities which can be used to further interrogate bacterial survival and participation in soil and rhizosphere communities.